Evaluation of the Relationship Between Placental Thickness and Obstetric Doppler Parameters During the Second Trimester - Emine Aydin; Ayca Nazli Bulut (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To determine whether there is a relationship between placental thickness and the umbilical artery and uterine artery Doppler evaluation in the second trimester. STUDY DESIGN: The placental thickness and the umbilical artery and uterine artery Doppler evaluations were recorded by a single operator for patients who were admitted for an obstetric follow-up or fetal anatomy screening at 18-28 gestational weeks. The relation between these variables was investigated by evaluating the patients only once.